Body Image, Self-Esteem, and Attitudes Toward Sexuality in Older Adults with Chronic Illnesses. - Özbay, Hediye; Utli, Adil; Filoğlu Ersü, Nilay (Archives of Sexual Behavior, 2025)
This study aimed to examine the effect of the association between body image and self-esteem levels on attitudes toward sexuality in older adults with chronic illnesses. The research was descriptive, cross-sectional, and correlational. The study sample comprised 1,004 people over the age of 65 who visited family health centers in a province in the east of Türkiye. The Older Person's Description Form, the Body–Cathexis Scale, the Rosenberg Self-Esteem Scale Short Form, and the Sexual Attitude Scale for Elderly People were used for data collection. For the data analysis, Pearson's r correlation test, simultaneous multiple linear regression, and binary logistic regression were employed. The mean age of the participants was 69.97 ± 5.74 years, and 66.9% were between 65 and 74 years of age. Furthermore, 53.8% of the participants were male and 56.2% had two chronic illnesses. It was found that the participants' age, body image, and self-esteem explained 84% of the total variance in their permissive attitudes toward sexuality. Furthermore, as the age of the older adults with chronic illnesses increased, there were negative effects on their permissive attitudes toward sexuality. However, as their body image and self-esteem levels improved, there was a positive effect on their permissive attitudes toward sexuality. These findings will be of benefit in encouraging and developing sexual health in older adults with chronic illnesses.